INOCULATION TECHNIQUE OF COLLETOTRICHUM GLOEOSPORIOIDES AFFECTS Phyllanthus niruri L. GROWTH AND BIOACTIVE COMPOUND SYNTHESIS - Irna Surya Bidara; Siti Himawati; Eka Nurhangga; Yomi Guno; Winda Nawfetrias (UIN Sunan Gunung Djati Bandung, 2026)
Colletotrichum gloeosporioides, an endophytic fungus, significantly enhances growth, defense against pathogens, and remediation of environmental stress in medicinal plants through induced resistance and phytohormone synthesis. The application technique affects the fungi's effectiveness in stimulating growth and inducing bioactive compounds in plants. Phyllanthus niruri is an Indonesian medicinal plant with bioactive compounds like flavonoids, alkaloids, terpenoids, lignans, polyphenols, tannins, and saponins. They offer health benefits like antioxidant, anti-inflammatory, analgesic, and antiviral effects. However, research on Phyllanthus-endophytic fungi from the Colletotrichum has not been reported. This study proposes that the application technique used for C. gloeosporioides affects the fungi's effectiveness in stimulating plant growth and inducing beneficial bioactive compounds. We experimented during 2022 and 2023 at an experimental greenhouse with two different methods of fungi inoculation: seed and planting medium. The study reveals that C. gloeosporioides inoculation impacts P. niruri growth differently, with seed inoculation promoting growth and planting medium inoculation potentially hindering it. Metabolic profiling through clustering analysis indicates that fungal inoculation significantly alters the plant's chemical composition, particularly increasing the abundance of specific alkenes, suggesting activation of defense mechanisms involving very long-chain fatty acids. It highlights the critical role of the inoculation method in shaping plant-microbe interactions and influencing the production of pharmacologically relevant compounds like steroids, diketones, alkanes, and alkenes, which may serve in the plant's defense responses and have beneficial impacts on human health. Therefore, optimizing inoculation strategies and understanding the underlying biological mechanisms are crucial for harnessing the potential benefits of microbial inoculants in agriculture and biotechnology.